Modeled and measured SARS-CoV-2 virus in septic tank systems for wastewater surveillance - Dong Li; Hunter Quon; Jared Ervin; Sunny Jiang; Diego Rosso; Laurie C. Van De Werfhorst; Brandon Steets; Patricia A. Holden (Journal of Water and Health, 2023)
SARS-CoV-2 wastewater surveillance (WWS) at wastewater treatment plants (WWTPs) can reveal sewered community COVID-19 prevalence. For unsewered areas using septic tank systems (STSs) or holding tanks, how to conduct WWS remains unexplored. Here, two large STSs serving Zuma Beach (Malibu, CA) were studied. Supernatant and sludge SARS-CoV-2 concentrations from the directly-sampled STSs parameterized a dynamic solid–liquid separation, mass balance-based model for estimating the infection rate of users. Pumped septage before hauling and upon WWTP disposal was also sampled and assessed. Most (96%) STS sludge samples contained SARS-CoV-2 N1 and N2 genes, with concentrations exceeding the supernatant and increasing with depth while correlating with total suspended solids (TSS). The trucked septage contained N1 and N2 genes which decayed (coefficients: 0.09–0.29 h−1) but remained detectable. Over approximately 5 months starting in December 2020, modeled COVID-19 prevalence estimations among users ranged from 8 to 18%, mirroring a larger metropolitan area for the first 2 months. The approaches herein can inform public health intervention and augment conventional WWS in that: (1) user infection rates for communal holding tanks are estimable and (2) pumped and hauled septage can be assayed to infer where disease is spreading in unsewered areas. HIGHLIGHTS Public communal septic systems were sampled over time for SARS-CoV-2.; SARS-CoV-2 sludge concentrations exceeded supernatant and followed TSS.; Sludge was sampleable during periodic disposal, but SARS-CoV-2 decayed while hauling.; Mass balance-based modeling well represented SARS-CoV-2 loading into septic systems.; The prevalence of COVID-19 infections was estimable.;